Mediation and interreligious discourse: prospects and challenges in resolving interreligious skirmishes in Malaysia - Ibrahim, Haslina; Maidin, Ainul Jaria (IIUM Press, 2020)
This article aims to promote mediation as an alternative dispute resolution mechanism to deal with interreligious skirmishes taking place in Malaysia. This is in view of the increasing statistics of interreligious disputes reported in the media. The reason for recommending interreligious mediation is due to its constructive nature in peacebuilding initiatives and its successful stories across the globe. The article discusses the potential actors of religious mediators and their requirements as well as the processes and conditions for a successful mediation. The article also highlights the need for certified training to make a credible mediator. Using mainly textual research, the article managed to gather and analyse the meaning and concept, historical background and the structure of mediation. Since mediation is new in Malaysia, the article found that the government’s role is crucial in its institutionalization; hence the article proposes that the Ministry of National Unity leads the initiative.